The Presence of Calcified Raphe Is an Independent Predictor of Adverse Long-Term Clinical Outcomes in Patients With Bicuspid Aortic Stenosis Undergoing Transcatheter Aortic Valve Replacement - Lee, Yung-Tsai; Yin, Wei-Hsian; Tsao, Tien-Ping; Lee, Kuo-Chen; Hsiung, Ming-Chon; Tzeng, Yun-Hsuan; Wei, Jeng (Frontiers in Cardiovascular Medicine, 2022)
Objective: Current guidelines recommend that transcatheter aortic valve replacement (TAVR) for bicuspid aortic valve (BAV) with aortic stenosis (AS) should only be performed in selected patients. However, we consider it even more crucial to identify what are the really important factors while determining long-term outcomes in BAV patients undergoing TAVR, which is precisely the aim of the present study. Methods: We retrospectively evaluated consecutive patients, who underwent TAVR with balloon-expandable Sapien XT or Sapien 3 valves (Edwards Lifesciences, Irvine, CA) for the treatment of severe Bicuspid AS. The primary end-point was major adverse cardiac and cerebral events (MACCE), i.e., mortality, non-fatal myocardial infarction (MI), disabling stroke, valve failure needing re-intervention, or clinically relevant valve thrombosis during follow-up. Results: A total of 56 patients, who underwent TAVR with Sapien XT (n = 20) or Sapien 3 (n = 36), were included. The device and procedural success rates were similar between the two TAVR valves; however, the newer-generation Sapien 3 yielded a trend towards better long-term clinical outcomes than the early-generation Sapien XT did (MACCE rates 35% vs. 11%, P = 0.071). In the multivariate Cox proportional hazards analyses, the presence of calcified raphe > 4mm was the only independent predictor of long-term MACCE (hazard ratio: 6.76; 95% confidence interval: 1.21 to 37.67; P = 0.029). Conclusions: TAVR performed by a skilled heart team, while using newer-generation balloon-expandable Sapien 3 valve, may yield better long-term clinical outcomes, compared to TAVR using early-generation Sapien XT valve. Moreover, the presence of calcified raphe > 4mm is an independent determinant of adverse clinical outcomes.